Modern Pedagogical Approaches in the System of Engineering Education - L. V. Orinina; I. V. Kashuba; N. V. Dyorina; E. V. Rabina (Moscow Polytechnic University, 2019)
The article aims at studying the specifics of the psychological and pedagogical competence of future engineers in the structure of the educational process and in relation to the use of innovative and effective educational technologies. At present, the general issues of humanization and pedagogical and methodological support of the educational process are of great importance in light of the need to increase the academic mobility of university graduates who choose to work at universities. The problem of insufficient level of their psychological and pedagogical competence development arises automatically. Psychological and pedagogical competence of a graduate means his (her) ability to mastering the basic material of the psychological and pedagogical unit, the ability to operate the acquired knowledge and put it into practice, mastering acquired skills in the conditions of concrete professional and pedagogical activity.This problem has several solutions. One of the most effective is the possibility of developing and introducing the programmes of advanced psychological and pedagogical training and professional retraining for future engineers specializing in engineering pedagogy.The purpose of the article is to view the effective approaches to the development of psychological and pedagogical competences among future engineers. The authors consider using of the modern IT-technologies to be a strong motivator in this process as well as gamification (role games and business games).As the key tasks of the teaching staff at technical university the following issues are regarded: creation of conditions for the disclosure by future engineers of their professional and personal resources; obtaining by future engineers the information necessary to increase the level of their psychological and pedagogical competence; acquisition of skills necessary for knowledge application in future professional activity; expanding the range of professional competencies of future engineers in the conditions of psychological and pedagogical design.One of the most important aspects of teacher's activity is reflection, self-evaluation. The authors present teachers' behavior patterns for reflection and formulate the recommendations for teaching future engineering teachers.Thus, the specificity of training future engineers with the focus on increasing their psychological and pedagogical competence is a complex multi-faceted process, specially organized in time and space, involving consideration of certain psychological and pedagogical, methodological and methodical patterns and aimed at developing professional qualifications of future engineering pedagogues.